Remoción de Cu (II) de aguas ácidas usando biomasa de las cáscaras de coco - Ángeles Suazo, Nataly Roxana (2022)
Conferencia de la 20th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Education, Research and Leadership in Post-pandemic Engineering: Resilient, Inclusive and Sustainable Actions”. hybrid event, Boca Raton, Florida- USA, junio 18 - 22.